Search for associated production of a Higgs boson and a single top quark in proton-proton collisions at root s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2019)
A search is presented for the production of a Higgs boson in association with a single top quark, based on data collected in 2016 by the CMS experiment at the LHC at a center-of-mass energy of 13 TeV, which corresponds to an integrated luminosity of 35.9 fb−1. The production cross section for this process is highly sensitive to the absolute values of the top quark Yukawa coupling, yt; the Higgs boson coupling to vector bosons, gHVV; and, uniquely, their relative sign. Analyses using multilepton signatures, targeting H → WW, H → ττ, and H → ZZ decay modes, and signatures with a single lepton and a bb¯ pair, targeting the H → bb¯ decay, are combined with a reinterpretation of a measurement in the H → γγ channel to constrain yt. For a standard model–like value of gHVV, the data favor positive values of yt and exclude values of yt below about −0.9yt SM.